THE EFFECT OF PAYLATER FEATURE, PERCEIVED EASE OF USE, AND FOMO ON IMPULSE BUYING DECISIONS ON THE SHOPEE APPLICATION AMONG THE BANTEN COMMUNITY: Shopee Paylater, Ease of Use, FOMO, Impulse Purchase - Anggit Yoebrilianti; Wulan Puspitasari; Nafiudin (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the influence of Paylater features, the perception of ease of use, and Fear of Missing Out (FOMO) on impulse purchase decisions on the Shopee application in the Banten community. The study used a quantitative approach with a survey method of 100 respondents selected through purposive sampling techniques. Data was collected using an online questionnaire and analyzed with Structural Equation Modeling (SEM) based on Partial Least Square (PLS) using SmartPLS 4.0 software. The results showed that simultaneously, the three independent variables had an influence of 52.5% on impulse purchase decisions with an R-Square value of 0.525. Partially, the results of the analysis showed that the Shopee Paylater feature did not have a significant effect directly on impulse purchase decisions (t = 1.116; p = 0.132). In contrast, the perception of ease of use had a significant effect (t = 2.032; p = 0.021), and FOMO had the most significant influence on impulse purchase decisions (t = 9.411; p = 0.000). These findings indicate that psychological factors and perceptions of ease of use of the platform are more dominant driving impulse buying behaviors compared to digital credit features